Servicios ambientales del Styzolobium deeringianum (mucuna) evaluado en cuatro tiempos de corte en Zungarococha Iquitos 2019 - Acosta Nunes, Gino Paolo (2024)
Was the work developed in the shop Agrostologico, located in Zungarococha to 45 minutes of the city of Iquitos, was the objective to evaluate the quantity of Carbon and the Efficiency Fotosintética that accumulates during its vegetative development the Styzolobiun deeringianum (Mucuna) evaluated at the 3er, 4to, 5to and 6to month, for what thinks about the problem that In what measure the evaluations carried out to the mucuna, does he/she have effect in the Capture of Carbon and Efficiency Fotosintética?, to achieve the objectives you employment the design of Complete Blocks at random, with four (4) treatments and three (3) repetitions. He/she was carried out the test of normality (Net) and of variancias homogeneity (Net and Pred), being normality and variancias homogeneity in the results, then he/she was carried out the parametric statistical analyses and the test of significancia of stockings, being obtained the following results; significancia exists in the court age, production of green matter, dry matter, efficiency Fotosintética and capture of carbon. Evaluated at 3er o'clock, 4to, 5to and 6to month in the shop Agrostologico. The court age also influences on the production of green matter (kg/m2), dry matter (kg/m2), efficiency Fotosintética and capture of carbon, being the cut to the 6to month that occupies the first place in comparison with the other treatments, with averages of (4.47 kg/m2), (0.99 kg/m2), (1.05) and (3.80) respectively. With respect to the outlined hypothesis this it is rejected and the Hypothesis of Alternating investigation is accepted, since the evaluations carried out according to the times of court if I influence significantly in all the studied variables.